Assamese Monkeys in Nagarjun Forest of Shivapuri Nagarjun National Park, Nepal - Chalise, Mukesh K; Ogawa, Hideshi; Pandey, Bishnu (Tribhuvan University Journal, 2013)
The population distribution of Assamese monkey Macaca assamensis were studied in Nagarjun forest of Shivapuri Nagarjun National Park, Nepal and data collected during Dec. 2013 and January 2014, by scan sampling methods along with transect walk through forest trails and ring-road of forest. Sevenbi sexual troops were observed in subtropical/lower temperate forest of Nagarjun forest especially around Raniban forest area. The observed smallest troop was with 9 individuals while the largest troop had 37 (41) individuals of different age. The average troop size is 20.57. Out of three broad age groups adults were 56.31% and immature 43.06% while infant alone were 18.06%. The sex ratio between male and female was 1:1.34. Plant usage for feeding and resting were also enumerated. Nagarjun forest troops use mostly tall trees for the night halts and resting in day time.